Studi Eksegesis Terhadap Kata ‘Tanpa Alasan’ (εἰκῇ ) Pada Kata ‘Marah’ Dalam Matius 5:22 Menurut Naskah Byzantium Dan Komparasinya Terhadap Novum Testamentum Graece (Nestle-Aland Edisi Ke-27) - Heny Heny (Sekolah Tinggi Teologi Adhi Wacana Surabaya, 2021)
Based on observations on the theological issues that occur at then current writer mendiskripsi is it some thing as background writing this work, including the following: first, the interpretation of the difference resulting from the use of the original language of the Bible is well seen from outside parties i.e. the view of the Islamic religion and views the Jewish religion, as well as from Parties within the IE view of Christianity itself, Second, more specifically the views of Islamic religious figures who say that the Bible is corrupted. K etiga, from among the Christian religion itself there is the memasalahkan process of translation and the translation of results from the original language texts are taken from the existing texts, translations and consider which one is superior (the original script approach) than others. For example there is one book called